Prioritizing long-acting injectable antiretroviral therapy among key populations: Perceptions of persons living with HIV who inject drugs, ART clinic staff, and policymakers in Vietnam - Minh X. Nguyen; Vivian F. Go; Adams L. Sibley; Hanna E. Huffstetler; Trang N.T. Do; Ha V. Tran; Le M. Giang; Teerada Sripaipan; William C. Miller; Joseph J. Eron; Cynthia L. Gay; Sarah E. Rutstein (PLoS ONE, 2025)
Objectives We explored perceptions of long-acting injectable (LAI) patient prioritization and decision-making among people who inject drugs (PWID) with HIV, HIV clinic staff, and policymakers in Vietnam. Methods From February to November 2021, we conducted 38 interviews with 19 PWID, 14 HIV clinic staff, and 5 policymakers in Hanoi, Vietnam. Interviews were coded and analyzed using thematic analysis to assess themes across participants. Results PWID highlighted the importance of medical providers in treatment decisions, while clinic staff stressed adequate counseling and patient choice. Non-patient participants viewed adherence to Ministry of Health guidelines as essential, and many clinic staff saw PWID as ideal for LAI due to suboptimal adherence. Policymakers, however, preferred prioritizing LAI based on viral suppression and adherence rather than risk behaviors. Conclusions This study reveals conflicting stakeholder views on LAI prioritization, suggesting a need for a more nuanced implementation approach to balance efficiency and fairness in low-resource settings.